2013
DOI: 10.3325/cmj.2013.54.362
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal exercise during pregnancy on abnormal fetal growth

Abstract: AimTo assess the effect of maternal physical activity during pregnancy on abnormal fetal growth.MethodsThe study group of 166 women in gestational week 6-8 exercised regularly three days per week at submaximal intensity during their entire pregnancy and the control group of 168 women received standard antenatal care. The main outcomes were macrosomia and intrauterine growth restriction.ResultsThe study group had a lower frequency of macrosomia in newborns (6.0% vs 12.5%, P = 0.048) and gestational diabetes (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 28 publications
2
112
0
4
Order By: Relevance
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 61%
“…The few studies that did demonstrate a significant beneficial effect of diet and/or physical activity all started the intervention relatively early, in the first trimester, before or near 13 weeks of gestation [31][32][33][34][35][36][37][38][39][40]. For example, among all the published studies to date on physical activity interventions for GDM prevention [41,42], the point estimate for the majority of studies indicate a beneficial effect, yet only those with the intervention starting early in the first trimester had statistically significant findings [33][34][35]38]. The same was true for intervention approaches that combined physical activity with diet modification [36,37,40], administered diet modification/supplement alone [39] or pharmacological intervention with metformin [31].…”
mentioning
confidence: 99%
“…Mode of exercise included walking, stationary cycling, aerobic dance, water gymnastics, and resistance training. Exercise intensity was assessed by heart rate monitors 19,20,[23][24][25][26][27][28][29][32][33][34][35][36]40,41,[43][44][45]47 and the Borg Scale of Perceived Exertion. 17,37,[42][43][44][45][46] Three studies did not report exercise intensity 31,38,39 and many did not give a precise intensity range (eg, less than 70% heart rate reserve).…”
Section: Resultsmentioning
confidence: 99%
“…When P values were not available for change-from-baseline outcomes such as gestational weight gain, 19,20 the standard deviation of the change was estimated using the correlation coefficient between preintervention and postintervention values from other studies in the review (Cochrane Handbook 16.1.3.2 18 ).…”
Section: Study Selectionmentioning
confidence: 99%
“…El beneficio no sólo es para la madre sino también para el feto, pues disminuye el riesgo de macrosomía y todo esto facilita un parto más fisiológico (26)(27)(28)(29). El aumento excesivo de peso y la dificultad de perderlo tras el parto suponen factores de riesgo en la aparición de complicaciones durante la gestación, el parto, la salud del feto y la futura salud de la madre (30)(31)(32).…”
Section: Introductionunclassified